Hydrogen‐Free Production of Green Diesel from Deoxygenation of Methyl Palmitate via Cross‐Metathesis with Bio‐Ethylene Using Supported WO 3 Catalyst - Mochamad Solehudin; Kanokwan Wengwirat; Pratya Promchana; Yingyot Poo‐arporn; Wanwisa Limphirat; Kittisak Choojun; Tawan Sooknoi (Chemistry - An Asian Journal, 2025)
) sites, yielding a C16-ene majority with trace amounts of C17-ene. Smaller hydrocarbons (<C15) are obtained as minor components from decarbonylation, hydrogen transfer, and cracking. The increased contact time (27-106 g h/mol) at 460 °C results in increased conversion (30%-87 %), green diesel (12%-57%), SAF (3.5%-12.7%), and bio-naphtha (1.3%-5.3%). Optimal green diesel production of 2.92 h⁻¹ with 73% selectivity can be achieved at 480 °C. SAF and bio-naphtha yields can be tuned by varying temperature from 460 to 500 °C. This provides a sustainable pathway for renewable liquid fuels without an external hydrogen supply.
Keywords: Catalysis and Hydrodesulfurization Studies; Catalysis for Biomass Conversion; Carbon dioxide utilization in catalysis